Impact of outreach programmes on the relationship between local people and parks. Perceptions of communities near Tarangire National Park, Tanzania - Franco P. Mbise; Timotheo Sosiya (Global Ecology and Conservation, 2023)
Understanding the impact of outreach programmes on local people and parks is vital for long-term park protection, especially in developing countries. This study assessed how community outreach programmes (COPs) can strengthen relationships between local people and Tarangire National Park (TNP). A questionnaire survey of 200 households from 4 villages (n = 50 households for each village) was used for data collection. The study results show that people with formal education were happier about activities initiated by COPs and were more likely to be willing to report poachers to park management. Furthermore, middle-aged and older people in the study area were happier on various activities initiated by COPs than young people. Seventy-eight percent (n = 156) of the respondents were happy with the conservation activities initiated by the Community Outreach Programmes. In addition, nearly half of the respondents (49%, n = 98) said they would report poachers to the park authority. When local people are happy about different activities related to conservation, they are more likely to be good custodians of nature and even more willing to report poachers to park management. Therefore, to enhance mutual cooperation between parks and local communities, people surrounding protected areas in different parts of the world should be actively involved in different conservation activities.